Carbon Dots from Citric Acid and its Intermediates Formed by Thermal Decomposition. Issue 51 (22nd August 2019) - Ludmerczki, Robert; Mura, Stefania; Carbonaro, Carlo Maria; Mandity, Istvan M.; Carraro, Massimo; Senes, Nina; Garroni, Sebastiano; Granozzi, Gaetano; Calvillo, Laura; Marras, Sergio; Malfatti, Luca; Innocenzi, Plinio
Abstract: Thermal decomposition of citric acid is one of the most common synthesis methods for fluorescent carbon dots; the reaction pathway is, however, quite complex and the details are still far from being understood. For instance, several intermediates form during the process and they also give rise to fluorescent species. In the present work, the formation of fluorescent C‐dots from citric acid has been studied as a function of reaction time by coupling infrared analysis, X‐ray photoelectron spectroscopy, liquid chromatography/mass spectroscopy (LC/MS) with the change of the optical properties, absorption and emission. The reaction intermediates, which have been identified at different stages, produce two main emissive species, in the green and blue, as also indicated by the decay time analysis. C‐dots formed from the intermediates have also been synthesised by thermal decomposition, which gave an emission maximum around 450 nm. The citric acid C‐dots in water show short temporal stability, but their functionalisation with 3‐aminopropyltriethoxysilane reduces the quenching. The understanding of the citric acid thermal decomposition reaction is expected to improve the control and reproducibility of C‐dots synthesis. Abstract : Understanding C‐dot formation : Synthesis of carbon dots based on citric acid needs to be carefully controlled to be reproducible and reliable, however, thermal degradation of citric acid is a complex process involving the formation of several intermediates during different dehydration and reduction processes. Thus, the formation of fluorescent C‐dots from citric acid has been studied as a function of reaction time by coupling infrared analysis, X‐ray photoelectron spectroscopy, liquid chromatography/mass spectroscopy (LC/MS) with the change of the optical properties.